Fault diagnosis in nonlinear hybrid systems - Zhirabok, Alexey; Shumsky, Alexey (Zielona Góra: Uniwersytet Zielonogórski)
The problem of fault diagnosis in hybrid systems is investigated. It is assumed that the hybrid systems under consideration consist of a finite automaton, a set of nonlinear difference equations and the so-called mode activator that coordinates the action of the other two parts. To solve the fault diagnosis problem, hybrid residual generators based on both diagnostic observers and parity relations are used. It is shown that the hybrid nature of the system imposes some restrictions on the possibility of creating such generators. Sufficient solvability conditions of the fault diagnosis problem are found. Examples illustrate details of the solution.
Keywords: hybrid systems; finite automata; mode activator; fault diagnosis; nonparametric methods